2013
DOI: 10.3747/co.20.1600
|View full text |Cite
|
Sign up to set email alerts
|

Panitumumab Monotherapy Compared with Cetuximab and Irinotecan Combination Therapy in Patients with Previously Treated KRAS Wild-Type Metastatic Colorectal Cancer

Abstract: Background: The survival benefit for single-agent anti–epidermal growth factor receptor (EGFR) therapy compared with combination therapy with irinotecan in KRAS wildtype (wt) metastatic colorectal cancer (mCRC) patients in the third-line treatment setting is not known. The objective of the present study was to describe the characteristics of, and to compare survival outcomes in, two cohorts of patients treated with either singleagent panitumumab or combination therapy with cetuximab and irinotecan. Methods: Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 19 publications
(30 reference statements)
0
7
0
1
Order By: Relevance
“…Only one retrospective study compared EGFR‐directed antibody therapy (Pmab) alone or in combination with chemotherapy (Cmab + I). In this study of 178 patients in British Columbia, Canada, all of whom were KRAS exon 2 wild‐type, the median OS favored combination therapy over monotherapy (8.3 vs 7.7 months) but this difference was not statistically significant [HR 1.29 (95% CI 0.77–2.14), p = 0.34] . TTD was not assessed and statistical power was very limited, with only 37 patients receiving combination therapy .…”
Section: Discussionmentioning
confidence: 86%
See 2 more Smart Citations
“…Only one retrospective study compared EGFR‐directed antibody therapy (Pmab) alone or in combination with chemotherapy (Cmab + I). In this study of 178 patients in British Columbia, Canada, all of whom were KRAS exon 2 wild‐type, the median OS favored combination therapy over monotherapy (8.3 vs 7.7 months) but this difference was not statistically significant [HR 1.29 (95% CI 0.77–2.14), p = 0.34] . TTD was not assessed and statistical power was very limited, with only 37 patients receiving combination therapy .…”
Section: Discussionmentioning
confidence: 86%
“…In this study of 178 patients in British Columbia, Canada, all of whom were KRAS exon 2 wild‐type, the median OS favored combination therapy over monotherapy (8.3 vs 7.7 months) but this difference was not statistically significant [HR 1.29 (95% CI 0.77–2.14), p = 0.34] . TTD was not assessed and statistical power was very limited, with only 37 patients receiving combination therapy . With a much larger sample size ( n = 1081), our study was better powered to detect an OS difference between combination and EGFR monotherapy.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…-FOLFIRI +/-bevacizumab ili afl ibercept ili ramucirumab bez obzira na status KRAS-a/NRAS-a (IA) ili -irinotekan +/-bevacizumab ili -FOLFIRI + cetuksimab ili panitumumab ako nisu primijenjeni u prvoj liniji kod tumora s KRAS-om/ NRAS-om divljeg tipa (IIA) ili -irinotekan + cetuksimab ili panitumumab ako nisu primijenjeni u prvoj liniji kod tumora s KRAS-om/ NRAS-om divljeg tipa (IIA). [52][53][54][55][56][57] Primjena treće linije kemoimunoterapije/kemoterapije rezervirana je za bolesnike dobra općeg stanja (ECOG 0 -2) i ovisi o ordiniranoj prethodnoj kemoimunoterapiji/ kemoterapiji.…”
Section: T4aunclassified
“…Different strategies aimed at inhibiting EGFR with small molecules (erlotinib and gefitinib) or with monoclonal antibodies (cetuximab and panitumumab) have been developed over the years in many cancer types [ 1 6 ]. Panitumumab (Vectibix, Amgen), a fully human antibody directed against EGFR, was initially approved in KRAS wild type (WT) metastatic colorectal cancer (mCRC) patients refractory to previous chemotherapy [ 7 , 8 ]. In biliary tract carcinoma (BTC), preclinical evidence of antitumor activity [ 9 ] and the lack of compelling therapies suggested that the combination of standard chemotherapy and EGFR inhibitors could be an attractive option to improve patient outcome [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%